Reshaping the Tumor Immune Microenvironment Based on a Light‐Activated Nanoplatform for Efficient Cancer Therapy. Issue 11 (7th February 2022) - Yang, Zebin; Luo, Yu; Yu, Huizhu; Liang, Kaicheng; Wang, Miao; Wang, Qigang; Yin, Bo; Chen, Hangrong
Abstract: The immunosuppressive tumor microenvironment (TME) always causes poor antitumor immune efficacy, prone to relapse and metastasis. Herein, novel poly(vinylpyrrolidone) (PVP) modified BiFeO3 /Bi2 WO6 (BFO/BWO) with a p–n type heterojunction is constructed for reshaping the immunosuppressive TME. Reactive oxygen species can be generated under light activation by the well‐separated hole (h + )–electron (e − ) pairs owing to the heterojunction in BFO/BWO‐PVP NPs. Interestingly, h + can trigger the decomposition of H2 O2 to generate O2 for alleviating tumor hypoxia, which not only sensitizes photodynamic therapy (PDT) and radiotherapy (RT), but also promotes tumor‐associated macrophages (TAMs) polarization from M2 to M1 phenotype, which is beneficial to decrease the expression of HIF‐1α. Importantly, such a light‐activated nanoplatform, combining with RT can efficiently activate and recruit cytotoxic T lymphocytes to infiltrate in tumor tissues, as well as stimulate TAMs to M1 phenotype, dramatically reverse the immunosuppressive TME into an immunoactive one, and further boost immune memory responses. Moreover, BFO/BWO‐PVP NPs also present high performance for computed tomography imaging contrast. Taken together, this work offers a novel paradigm for achieving O2 self‐supply of inorganic nanoagents and reshaping of the tumor immune microenvironment for effective inhibition of cancer as well as metastasis and recurrence. Abstract : An oxygen self‐supplying nanoplatform for enhancing PDT/RT and reshaping the tumor immune microenvironment exhibits effective inhibition of the growth of both primary, metastatic, and recurrent tumors. Light activation of hole generation can trigger the decomposition of H2 O2 to produce oxygen for alleviating tumor hypoxia, which not only sensitizes radiotherapy and photodynamic therapy, but also promotes the TAMs' polarization to M1 phenotype, and decreases the expression of HIF‐1α.